Some Questions Ensuring of Safety when carrying out the Reform of Power Institutes of the State - Andrey Andreevich Kovalev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In article the author considers questions of safety which can be staticized in case of implementation of reform of power institutes of the power. In present period concentration of law enforcement agencies and their integration into a single whole can lead aggravations of a foreign policy provision of Russia to positive results if such reform is carried out with the maximum efficienc y rate.